Review of non‐invasive body contouring devices for fat reduction, skin tightening and muscle definition. (6th June 2019) - Mazzoni, Daniel; Lin, Matthew J; Dubin, Danielle P; Khorasani, Hooman
Abstract: Non‐invasive body contouring is a rapidly growing field in cosmetic dermatology. Non‐invasive contouring devices improve the body's appearance through the removal of excess adipose tissue, particularly in areas in which fat persists despite optimal diet and exercise routine. The technology can also be used for skin tightening. This article reviews the five FDA‐approved non‐invasive body contouring modalities: cryolipolysis, laser, high‐intensity focused electromagnetic field, radiofrequency and high‐intensity focused ultrasound. These devices have emerged as a popular alternative to surgical body contouring due to their efficacy, favourable safety profile, minimal recovery time and reduced cost. Although they do not achieve the same results as liposuction, they are an attractive alternative for patients who do not want the risks or costs associated with surgery. When used appropriately and correctly, these devices have demonstrated excellent clinical efficacy and safety.